THE IMPACT OF INNOVATIVE CSR MANAGEMENT ON THE IMPLEMENTATION OF GREEN HUMAN RESOURCE PRACTICES, GOVERNANCE, AND HUMAN RIGHTS TOWARD SUSTAINABLE BUSINESS IN PUBLICLY LISTED COMPANIES - Suwandi; Fathan Zidni Imawan (Pena Cendekia Insani, 2026)
This study aims to analyze the impact of innovative CSR management on sustainable business performance. The research examines 16 coal mining companies and 16 palm oil plantation companies listed on the Indonesia Stock Exchange (IDX), while considering the mediating roles of green human resources and respect for human rights. A quantitative approach was employed with publicly listed companies as the unit of analysis, and data were collected through structured document-based observation derived from corporate annual reports and sustainability reports. Linear regression analysis using SPSS software indicates that innovative CSR management does not yet have a significant direct effect on sustainable business performance. However, CSR is found to have a positive and significant influence on respect for human rights, highlighting its role in internalizing ethical values at the organizational level. Simultaneous testing results show that the combination of CSR and human resources explains only a small proportion of the variance in sustainable business, with human resources demonstrating a significant but negative partial effect. These findings suggest that the impact of CSR on business sustainability is indirect and requires stronger mediating mechanisms. This study contributes theoretically to the development of mediation-based CSR models and offers practical implications for companies in designing more integrated CSR strategies to support sustainable business practices.